Business strategies in a transitional economy : a case study of CIBA speciality chemicals in Vietnam. - Lee, Laolotawan Yang. (2008)
The textile and garment industry is one of Vietnam's significant industry in its drive towards a developed nation. Through the implementation of the Doi Moi policy, Vietnam achieved remarkable economic progression and made a major shift towards export-oriented development. Today Vietnam is one of the fastest growing economies in South East Asia region attracting a significant foreign direct investment in various industries. However the future of Vietnam and its competitive advantage depends heavily on its accession to WTO in January 2005.